2014
DOI: 10.1111/1471-0528.13074
|View full text |Cite
|
Sign up to set email alerts
|

Associations of maternal circulating 25‐hydroxyvitamin D3 concentration with pregnancy and birth outcomes

Abstract: Main outcome measures Gestational diabetes mellitus (GDM), preterm delivery, caesarean section, fetal growth restriction (FGR) and small-for-gestational age (SGA), anthropometric birth outcomes including weight, length and head circumference (HC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
92
5
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 45 publications
15
92
5
3
Order By: Relevance
“…In our study we did not found any significant difference between the two groups with respect to the total number of maternal and fetal complications similarly Rodriguez et al 19 did not find any association between maternal circulating 25(OH)D3 concentration in pregnancy with GDM and preterm delivery. In our study the serum vitamin D levels in both the groups had no impact on the neonatal birth weight.…”
Section: Discussion:-supporting
confidence: 66%
“…In our study we did not found any significant difference between the two groups with respect to the total number of maternal and fetal complications similarly Rodriguez et al 19 did not find any association between maternal circulating 25(OH)D3 concentration in pregnancy with GDM and preterm delivery. In our study the serum vitamin D levels in both the groups had no impact on the neonatal birth weight.…”
Section: Discussion:-supporting
confidence: 66%
“…The score for one article, however, was unable to be evaluated because the full text was not available, and three RCT had low risk of bias. Table 1 lists the characteristics of the 18 observational studies 9,[12][13][14][15][16][17][18][19][20][21][22][23][24][30][31][32] and six RCT. [33][34][35][36][37][38] There was some disparity in the definition of PTB between studies.…”
Section: Literature Searchmentioning
confidence: 99%
“…11 Most observational studies, however, did not show a significant relationship. 9,[12][13][14][15][16][17][18][19][20][21][22][23][24] A trial of vitamin D supplementation suggested that 25-OHD serum concentration > 100 nmol/L (vs <50 nmol/L) could significantly reduce the risk of PTB. 25 Other studies, however, did not obtain the same results.…”
Section: Introductionmentioning
confidence: 99%
“…Different fetal growth patterns and body proportions may lead to the same birth weight. Not much is known about the direct effects of maternal vitamin D status on fetal growth and development patterns in healthy populations (8,(10)(11)(12)(13). The inconsistent results from previous studies may be explained by differences between study populations.…”
Section: Introductionmentioning
confidence: 97%
“…Also, vitamin D is important for placental function, calcium homeostasis, and bone mineralization, which are all important determinants for fetal growth and development (5,6). Thus far, to our knowledge, most published studies that have focused on the associations of maternal vitamin D status during pregnancy with fetal development have been based mainly on birth weight and have shown inconsistent results (7)(8)(9). However, birth weight is just a proxy for fetal growth and development.…”
Section: Introductionmentioning
confidence: 99%